Product's promotion patterns and their effects on consumers' purchase intentions, brand loyalty and attitude (2006)
This research investigated the influence of promotional patterns of coca-cola products on purchase intentions, loyalty and attitude of consumers in Nigeria. Ninety randomly selected social science undergraduates of a major Nigerian university participated in the study. Participants were randomly assigned to three new coca-cola television promotions, namely, dream trip: open and win: and collect and win. The study was in a human laboratory of the university’s psychology department. Following timed viewing of the product’s promotions on television, participants completed a structured questionnaire that tapped information on four key areas, namely, socio-demographics, consumer attitude, purchase intentions and brand loyalty. A one-way analysis of variance tested each of three hypotheses. Result showed that there was no significant different in the purchase intentions of participants exposed to coca-cola open and win and collect and win promotions. Similarly, there was no significant difference in the brand loyalty of participants exposed to the coca-cola dream trip promotion and participants exposed to the coca-cola collect and win promotions. Findings of the study were discussed in line with conceptual and practical trends involving the subject areas investigated.